Relação de estudantes surdo com os conhecimentos escolares : percursos e percalços no aprendizado da química - Santos, Aline Nunes (2017)
This research is the result of the questions and concerns that emerged at the end of the school year of 2015, from the first professional experiences as a professor of Chemistry at a public school in the backlands of Bahia. The institution was attended by two deaf female students and a male one who, after the disapproval in that year, were in situation of school abandonment in the following year. This paper aims to understand the relationship established with the school and scientific scholarly knowledge, specifically Chemistry, by a couple of deaf brothers, in a situation of school failure. In it, studies on the education of the deaf, proposed by Sá, Skliar and Perlin, were used as theoretical reference. In order to understand of the relation established by it, the notion of the relation with the knowing in Charlot was used, and the methodological trajectory is based on qualitative research, based on Bogdan and Biklen, having as subject of the research the deaf brothers, their parents, the teacher of the discipline, a sister and three of their classmates. Data collection was carried out through an interview, which allowed us to conclude that the relationship maintained by students with the school was based on the perspective of learning (reading and writing) as a mean of communication with hearing people; and for these students, going to school is linked to aspects of socialization. In turn, the relationship with scientific scholarly knowledge, especially in High School, in which their abstraction and language become more complex, and the ignorance of Libras by these students and their teachers have led them to a situation of school failure. Thus, the relationship with the world of Chemistry presents elements of the identified situation, even if the teacher has sought strategies to minimize such failure.